PFC2D-Based Analysis of the Effect of the Axial Loading Rate on the Mechanical Properties of Backfill - Wang Kun; Fu Jian-Xin; Wang Yu (Advances in Materials Science and Engineering)
The unloading failure process in mining engineering scenarios is similar to the loading failure process at different loading rates indoor. To clarify the relationship between the mechanical properties of backfill and the loading rate, a particle flow code 2D-based numerical simulation was performed to establish the backfill model, and tests involving five loading rates were conducted. The following results were obtained: (1) the compressive strength of the backfill body increases linearly with the increase in the loading rate. The peak strain increases in an S-shaped manner, and the modulus of elasticity first increases and then decreases. (2) The evolution of cracks is similar to that of damage energy consumption, and a smaller rate means that the curve’s inflection point arrives earlier. (3) Tensile failure is the dominant failure mode. As the rate increases, the model destruction mode transforms from single to multiple failures, and the crack distribution becomes denser. (4) The backfill body exhibits a uniform destruction form at all loading rates. However, the difference in the loading rate leads to different energy consumption growth rates and total energy consumption.